2021
DOI: 10.5604/01.3001.0015.3944
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and low levels of physical activity are associated with a decreased health-related quality of life in postmenopausal women: a Wroclaw pilot study

Abstract: Background: Menopause is associated with numerous somatic dysfunctions, an increased risk of chronic diseases, and complications in the mental and social components of health that lower the quality of life (QoL). Obesity and related comorbidities affect over 60% of postmenopausal women in Poland. A significant role for systematic physical activity (PA) in the prevention of dysfunctions and chronic diseases, including obesity and mental disorders, has been observed previously. A low level of PA is observed acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…This result is consistent with that of a previous study that showed that the majority of the female participants did not engage in physical activity (14,32). By contrast, Lewandowska et al (19) reported that the majority of the participants in their study had an adequate level of exercise, that is, more than 600 metabolic equivalents min/week.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This result is consistent with that of a previous study that showed that the majority of the female participants did not engage in physical activity (14,32). By contrast, Lewandowska et al (19) reported that the majority of the participants in their study had an adequate level of exercise, that is, more than 600 metabolic equivalents min/week.…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to that of a previous study in Jordan that reported that most of the female participants had a BSC degree (1,8). Previous studies also found that most of the female participants completed primary education or had an education level that was below high school (9,19,25,32,33,41,43).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations